1980 Survey of Doctoral Programs in Accounting in the United States. - Crum, William F. (The Accounting Review, 1981)
ABSTRACT: This paper updates information on accounting education reported in previous surveys published in 1968, 1971, 1974, and 1978. It was carried out as part of an assignment made by the Committee on Supply of Doctoral Students of the American Accounting Association, of which committee the author was a member. Data are provided on schools offering doctoral degrees, candidates in coursework stage, candidates in dissertation stage, degrees awarded between 1977 and 1979, and a tabulation of number of foreign students active in doctoral programs. Doctoral degrees granted in 1977 rose slightly above 1976. The number increased materially in 1978, but fell back to near 1976 levels in 1979. An increase is forecast for both 1980 and 1981. Total enrollment in doctoral degree programs has increased 38 percent since 1969, with the number of degrees granted increasing only 14 percent in the same period.